The Basic Department as the Adaptation Tool of Students to the Professional Environment - Alexandrovna Shindina, Tatiana; Vladimirovna Knyazeva, Nina; Vladimirovna Usmanova, Natalia; Dmitrievna Chuvashova, Anna (International Journal of Engineering and Technology, 2018)
The paper is devoted to the issues of students' adaptation to the professional environment. Professional adaptation is considered as a combination of two aspects: social and production. It is determined that the use of basic departments with applied bachelor programs can be one of the effective ways for preparing students who can easily adapt to some professional environment. As an example, the experience of the Department â€œAutomobiles and Automotive Serviceâ€ of South Ural State A university under Reginas company group is considered. A questionnaire was conducted, in which students enrolled in this basic department and students from related specialties took part. As a result of the research it was proved that the training at the basic department develops in students a steady interest and understanding of the importance of their future profession, which makes professional adaptation easier.Â Â Â